Selective Termination of Pregnancy (The Hastings Center report, 1988)
Ms. Q is a thirty-year-old woman who is pregnant for the first time, having spent several years in a local infertility program. She had been treated previously with clomiphene citrate, a fertility drug that increases the incidence of multiple births among those who subsequently become pregnant from 1 percent to 8 percent. Dr. G, the physician who prescribed the drug, had indicated to the patient that its use involved “some risk of multiple gestation.” At nine weeks gestation, ultrasound reveals the presence of triplets. After discussion with her husband, Ms. Q asks Dr. G to terminate two of the fetuses. She says she really wants to have a child and “be a good mother,” but doesn't feel capable of caring for more than one child at a time. Even though all three fetuses appear healthy, her preference is to abort all rather than have triplets. A technique similar to amniocentesis (in which the uterine cavity is entered) has been used to terminate selectively a defective fetus, when a serious fetal anomaly, such as Down syndrome, occurs in a multiple gestation. This technique could be used to terminate two of the triplets, but it entails an incremental risk of miscarriage. Legally, Dr. G could: (1) terminate the pregnancy through a standard method of abortion; (2) selectively terminate the gestation of two of the triplets; (3) refuse to terminate the pregnancy, with transfer of care to a physician who is willing to do so. Should Dr. G acquiesce in Ms. Q's request? Is this request morally valid?